(3GdJehjd GdESdGej hOhQ GdbWGY GdNGU (B/s - (3GdSQWGhj, aDGO YHO GddWjas ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 1999)
(3GdeGd hGdHfhc GdESdGejI,GdJehjd,YbhO GdJHQY hGdGQJaGb,YbhO GdJehjd GdGSJKeGQjs
(3HHdjhZQGajG(B:(3U(B.313-320s
Keywords: (3GdGbJUGO GdGSdGejs